Research on Book Cover Design in National Character (Herald of Journalism, 2021)
This article discusses the place and role of book covers in the art of publishing. It was noted that even if similar genres and trends exist at all times, creative approaches may differ depending on the cultural characteristics of each country.The purpose of this scientific article is to study the “appearance” of information, in our case, the importance of book cover design, since based on this the reader decides whether to read the information provided or not.The main idea of the study is to compare differences in cover design depending on the national char- acteristics of each country. The article examines the features of modern book illustration and compares several well-known examples.The authors of the article, during studying the topic, used general scientific research methods, in particular: the comparison method, methods of analysis and synthesis, content analysis, cognitive analysis. Theoretical studies and conclusions of foreign and domestic scientists have been obtained. Research results have shown that the cover is a “mirror” of the content of the book. It is decorative and even plays an important role in the marketing of the book, helping to better attract readers. A designer, who creates the appearance of a book, always sets himself many tasks: one should take into account the interests and needs of a potential reader, model the state of his relationship with the book, present the goals and principles of the structure of this type of publication.The design of the book today has undergone significant changes: from the official design of the cover to artistic unity. The materials and results of this work can be used in teaching the art of design, in the training of specialists in book design; in the field of art in general, in the research and practice of art historians, artists, cultural studies.Key words: book graphics, book publishing, design, book cover, peculiarities of national design.